Numerical Analysis of Ground Settlement Patterns Resulting from Tunnel Excavation in Composite Strata - Huijuan Deng; Ping Cao; Yinzhu Liu; Zhizhen Liu; Gang Meng; Zhi Fan; Weiping Xie (Applied Sciences, 2022)
Cross-river twin tunnels are prone to deformation and uneven settlement of the surrounding soil due to the complexity of the strata crossed, which has a negative impact on the tunnel structure. A numerical calculation model was established using the COMSOL Multiphysics to study the effects of twin tunnel excavation in composite strata on the ground settlement and the ground settlement pattern. The results indicated that after the construction of the twin tunnels is completed, the ground settlement above the first tunnel is slightly larger than the ground settlement above the second tunnel. The further the spacing between the two tunnels before and after excavation, the smaller the amount of ground settlement and the impact on the surrounding soil. The ground settlement value increases with the increase in burial depth, and the ground settlement curve gradually changes from a W-shaped curve to a V-shaped curve. As the distance between the two tunnels increases, the maximum settlement value of the settlement curve gradually decreases, and the ground lateral settlement curve changes from V-shaped to W-shaped. The higher the water level on the riverbed side, the greater the settlement value of the ground.